SERUM ANTI-OXLDL ANTIBODIES IN PATIENTS WITH ANGIOGRAPHICALLY CONFIRMED CORONARY ARTERY DISEASE - Tosheska-Trajkovska, Katerina; Kostovska, Irena; Emin, Melda; Ampova, Hristina; Manev, Nikola; Zimbakov, Zan; Kerala, Coskun; Bogdanska, Jasna; Topuzovska, Sonja (Journal of Morphological Sciences, 2023)
Cardiovascular disease (CVD) remains the leading cause of death worldwide. Oxidized low density lipoprotein (oxLDL) is believed to be central to the atherosclerotic cascade. Oxidative modification of LDL induces immunogenic epitopes in the LDL molecule, and the presence of antibodies against oxidized LDL (anti-oxLDL) has been demonstrated in human sera. Anti-oxLDL titer not only can predict a presence of atherosclerotic CAD but may also be a marker of plaque instability. The aim of this study was to measure the concentration of anti-oxLDL in patients with angiographically confirmed coronary artery disease (CAD). Ninety patients with coronary artery disease and 90 controls were included in the study. Patients were selected according to the positive result of coronary angiography. Total cholesterol, triglycerides, HDL-c and LDL-c were determined on Roche C311 Cobas Analyzer and OxLDLD and anti-oxLDL were determined with sandwich ELISA technique. We find significant difference between CAD patients and controls regarding OxLDL (p< 0.001). Serum anti OxLDL antibodies were correlated with LDL-c and we found significant correlation (p<0.05) in the CAD group. The regression model showed that the variables  Age, BMI, DBP, SBP, Total cholesterol, HDL-c LDL-c and TG explained 30.39% of the variance from the variable  anti-ox-LDL . Our results show that serum levels of ox LDL are associated with presence of CAD and with the lipid parameters. Keywords: cardiovascul ar disease, coronary artery disease, anti oxLDL, LDL.